2023
DOI: 10.1108/bij-10-2022-0670
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability 4.0 in services: a systematic review of the literature

Abstract: PurposeThis paper aimed to identify the impact that Industry 4.0 can have on the service sector and how its combination can generate benefits for Sustainability 4.0 in the context of the Triple Bottom Line.Design/methodology/approachA Systematic Literature Review (RSL) was developed using the following combinations of keywords on the Web of Science and Scopus databases: Industry 4.0 And Sustainability, Industry 4.0 And Service, and Industry 4.0 And Sustainable Development, in which 24 papers were selected.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Finally, the third part assessed customer perception regarding industry 4.0 (I4.0), sustainability, and the benefits provided by these technologies in the banking sector. This last stage, based on the study by [13] in the services sector, totaled 55 questions. The 55 questions were divided into 23 questions related to the economic dimension, 18 questions linked to the social dimension, and 14 questions related to the environmental dimension.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the third part assessed customer perception regarding industry 4.0 (I4.0), sustainability, and the benefits provided by these technologies in the banking sector. This last stage, based on the study by [13] in the services sector, totaled 55 questions. The 55 questions were divided into 23 questions related to the economic dimension, 18 questions linked to the social dimension, and 14 questions related to the environmental dimension.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, based on the studies of [13] who carried out a systematic review of the literature to understand the impact of industry 4.0 (I4.0) on the services sector and its contribution to sustainability 4.0, under the principles of the triple bottom line (economic, social, and environmental dimensions). The research by the authors identified 100 general benefits at this intersection, which were categorized into 54 benefits for the economic dimension, 25 for the social dimension, and 21 for the environmental dimension.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations